(3eSGfjO CHj MfjaI GdEeGes - (3CHh GdeDjO GdNhGQRej , eMeO Hf eMehO Hf eMeO Hf MSf, CHh GdeDjO GdNhGQRej,J (B655 (3g` s ((3Ydi Hf eMeO Gdbje s)
(3ChdgG (B:s
(3ef Chd GdcJGH s
(3BNQgG (B:s
(3Edi GdHGH GdKGfi YTQ ai GdMLQ s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B87 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B5s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B99 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs